Cover Picture: Structural Preferences in Phosphanylthiolato Platinum(II) Complexes (ChemistryOpen 1/2016). Issue 1 (3rd February 2016) - Duran, Josep; Polo, Alfonso; Real, Julio; Benet‐Buchholz, Jordi; Solà, Miquel; Poater, Albert
Abstract : The cover picture shows phosphanylthiolate ligand coordination on a platinum(II) center to give only the bischelate cis ‐P, P isomer when the ligand/Pt ratio is 2, whereas a trinuclear unexpected complex is achieved with a ligand/Pt ratio of 1. Here, the synthesis and structural determination is combined with density functional theory (DFT) calculations to rationalize the reaction mechanistically and through conceptual DFT. The exciting point of this study is that it opens the door to test new experimental pathways to monitor the preferred cis or trans arrangement of bidentate ligands to platinum. (Legend: H‐white, C‐black, P‐purple, S‐yellow, Cl‐green, Pt‐blue.) More information can be found in the Full Paper by Alfonso Polo, Albert Poater et al. onpage 51 in Issue 1, 2016 (DOI:10.1002/open.201500136 ).